Challenges in the Mold Flux Design: Development of F‐Free Fluxes and Fluxes for Casting of High‐Al Steel. Issue 3 (1st June 2021) - Yang, Jian; Wang, Lin; Wang, Qi; Zhang, Jianqiang; Sasaki, Yasushi; Zhang, Chen; Cai, Dexiang; Ostrovski, Oleg
Abstract : A significant research effort is directed toward development of F‐free fluxes to decrease an environmental impact of steel continuous casting. Another challenging problem in the mold flux design is their stability in the casting of high‐aluminum steel. This article summarizes the results of a study of F‐free CaO–SiO2 ‐based fluxes and CaO–Al2 O3 ‐based fluxes for the continuous casting of high‐Al steels, obtained at the University of New South Wales, Sydney, in close collaboration with the Baosteel Research Centre, China. This article discusses melting properties, viscosity, flux stability, crystallization, and heat transfer of F‐free CaO–SiO2 ‐based fluxes and CaO–Al2 O3 ‐based fluxes, and the effect of high‐Al steel–flux reaction on the flux properties. Melting properties of fluxes are determined by the hot stage microscopy method. Viscosity is measured using rotating cylindrical viscometer. Solidification of mold fluxes is examined using single and double hot thermocouple techniques (SHTT and DHTT, respectively). Continuous cooling and isothermal SHTT experiments are used to construct continuous cooling transformation (CCT) and time‐temperature transformation (TTT) diagrams. Heat transfer of mold fluxes is examined using an IR emitter technique. The properties of F‐free CaO–SiO2 ‐based fluxes and CaO–Al2 O3 ‐based fluxes are compared with the properties of industrial mold fluxes. Abstract : This article summarizes the results of a study of F‐free CaO–SiO2 ‐based fluxes and CaO–Al2 O3 ‐based fluxes for casting of high‐Al steels at the University of New South Wales, Sydney, in close collaboration with the Baosteel Research Centre, China. This article discusses melting properties, viscosity, flux stability, crystallization, and heat transfer of F‐free CaO–SiO2 ‐based fluxes and CaO–Al2 O3 ‐based fluxes.